Learn by doing as a didactic strategy through the codecademy web portal in pedagogical practice to promote creative thinking and significant learning in students (2019)
The work developed is action research type, framed in the qualitative paradigm. It designs a didactic strategy for the development of a different pedagogical practice to the traditional one that allows a greater autonomy in the student during the learning process, since the apprehension of knowledge is done in a more personal and practical way. The didactic proposal is developed from the diagnosis of the student's creativity and their ability to interact with academic platforms. Its implementation allows the student to learn by doing in a process of trial, error and correction in order to promote creative thinking while achieving meaningful learning.